PENGGUNAAN TEKNIK MAKE A MATCH DENGAN MEDIA FLASHCARD DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA TENTANG BILANGAN ROMAWI PADA SISWA KELAS IV SDN 2 KEBUMEN TAHUN AJARAN 2014/2015 - Aftariawan, Yan (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application of Make a Match Technique Using Flashcard Media in Improving Mathematics Learning about Roman Numeral for the Fourth Grade Student of SDN 2 Kebumen in the Academic Year 2014/2015. The objective of this research are to describe and improve mathematics learning about roman numeral for the fourth grade students in the elementary school, and find problems and solutions in the application of Make a Match technique using flashcard media. This research is a collaborative Classroom Action Research conducted for 3 cycles with phases of planning, action, observation, and reflection. Subjects were fourth grade students of SD Negeri 2 Kebumen, totaling 24 students. Data collection techniques used tests, observations, interviews, and documentation. Validity of the data used triangulation of sources and triangulation of techniques.The conclusion of this research is the application of Make a Match technique using flashcard media can improve mathematics learning about roman numeral for the fourth grade students of SDN 2 Kebumen. Keywords: Make a Match, flashcard, Mathematics Abstrak: Penggunaan Teknik Make a Match dengan Media Flashcard dalam Peningkatan Pembelajaran Matematika tentang Bilangan Romawi pada Siswa Kelas IV SDN 2 Kebumen Tahun Ajaran 2014/2015. Tujuan penelitian ini adalah untuk mendeskripsikan dan meningkatkan pembelajaran Matematika tentang bilangan Romawi siswa kelas IV SD, serta menemukan kendala dan solusi dalam penggunaan teknik Make a Match dengan media flashcard. Penelitian ini merupakan penelitian tindakan kelas kolaboratif yang dilaksanakan dalam 3 siklus dengan tahapan perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian adalah siswa kelas IV SDN 2 Kebumen yang berjumlah 24 siswa. Teknik pengumpulan data berupa observasi, wawancara, dan tes. Validitas data menggunakan triangulasi sumber dan teknik. Kesimpulan penelitian ini adalah penggunaan teknik Make a Match dengan media flashcard dapat meningkatkan pembelajaran Matematika tentang bilangan Romawi pada siswa kelas IV SDN 2 Kebumen. Kata Kunci: Make a Match, flashcard, Matematika